1989
DOI: 10.1016/0168-6445(89)90032-6
|View full text |Cite
|
Sign up to set email alerts
|

Microbial lectin cofunction with lytic activities as a model for a general basic lectin role

Abstract: Lectins are ubiquitous proteins, which exhibit a specific and reversible sugar-binding activity. They react with glycosylated macromolecules and cells and may coaggragate them and lead to their lysis or alterations. Various lectin biological effects are well known, but their basic biological function is considered as yet unknown. In the present review, an experimental evidence and theoretical considerations are forwarded for supporting our suggestion that the general basic lectin or lectinoid (lectin-like prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

1991
1991
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 32 publications
(67 reference statements)
2
12
0
Order By: Relevance
“…The hetnolytic and hemagglutinating activities of T. dentieola were shown to be closely related, with regard to their location, kinetic of production and heat stability. These results tend to support the recent hypothesis of Gilboa-Garber & Garber (6). They suggested that lectin-lysin pairs may reside in the satne molecule or in linked subunits on the cell surface of mieroorganisms.…”
Section: Discussionsupporting
confidence: 89%
“…The hetnolytic and hemagglutinating activities of T. dentieola were shown to be closely related, with regard to their location, kinetic of production and heat stability. These results tend to support the recent hypothesis of Gilboa-Garber & Garber (6). They suggested that lectin-lysin pairs may reside in the satne molecule or in linked subunits on the cell surface of mieroorganisms.…”
Section: Discussionsupporting
confidence: 89%
“…The initial event in the pathogenesis of most bacterial infectious diseases is microbial invasion of host cells after the microorganisms adhere to some host tissues, either directly or via some intermediary microorganisms [1]. Actinobacillus actinomycetemcomitans, a periodontopathic bacterium, has been implicated in the pathogenesis of several forms of periodontitis, and extracellular components from the bacterium are known to be potent mediators of its adherence to human oral epithelial cells [2].…”
Section: Introductionmentioning
confidence: 99%
“…This interaction may involve Iectins, as in the case of the Rhizobium-legume symbiosis (Diaz et al, 1986). The role of Iectins in this process may be related to the activity of hydrolytic enzymes in that lectin may act as a cofactor which enables key lytic activities (Gilboa-Garber & Garber, 1989). There is evidence that mycorrhizal roots possess higher pectin esterase and endopolymethyl galacturonase activities than non-mycorrhizal roots (Garcia-Romera et al, 1991).…”
Section: Introductionmentioning
confidence: 99%